High-corrosion-resistance magnesium alloy plate with filiform corrosion characteristic and preparation method of high-corrosion-resistance magnesium alloy plate

By adding Sc, Y and Mn elements to the magnesium alloy, and suppressing local pitting corrosion through alloy composition design and microstructure regulation, the filamentous corrosion characteristics of magnesium alloy are achieved, solving the problem of poor corrosion resistance of magnesium alloy and significantly improving its corrosion resistance and mechanical properties.

CN119663081AActive Publication Date: 2025-03-21SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202510179496.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-21
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

The corrosion resistance of magnesium alloys is poor, especially in humid and salt-containing environments, which is not as good as that of aluminum alloys and steel materials, resulting in the limitation of magnesium alloys in practical applications.

Method used

Through alloy composition design and microstructure regulation, local pitting of magnesium alloy is inhibited, making it show filamentous corrosion characteristics that develop along the substrate surface. The method includes adding a small amount of Sc, Y and Mn elements to the Mg-Al alloy to form a diffuse Mg17Al12 phase, and refining the grains through multi-pass rolling and heat treatment processes to improve the corrosion resistance of the alloy.

Benefits of technology

The high corrosion resistance of magnesium alloy is achieved, local pitting corrosion occurs, and the corrosion resistance and mechanical properties of the alloy are significantly improved, making it suitable for applications in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663081A_ABST
    Figure CN119663081A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal materials, and particularly relates to a high-corrosion-resistance magnesium alloy plate with filiform corrosion characteristics and a preparation method of the high-corrosion-resistance magnesium alloy plate. Based on the total amount of the magnesium alloy plate, the magnesium alloy plate is prepared from the following elements in percentage by mass: 6 to 9 percent of Al, 0.05 to 0.15 percent of Sc, 0.05 to 0.15 percent of Y, 0.05 to 0.15 percent of Mn and the balance of Mg and inevitable impurity elements; the preparation method of the alloy comprises the following steps: smelting an alloy cast ingot, carrying out solution treatment on the cast ingot, extruding into a plate, and then carrying out multi-pass rolling treatment and aging heat treatment regulation. The magnesium alloy plate has a phase structure of a dispersed Mg17Al12 phase, the corrosion behavior of the magnesium alloy plate is typical filiform corrosion characteristics, and compared with traditional pitting corrosion, the magnesium alloy plate has the advantages of being small in corrosion depth and small in destructiveness. The magnesium alloy plate provided by the invention has excellent mechanical properties and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal materials, and in particular relates to a high corrosion-resistant magnesium alloy plate with filamentary corrosion characteristics and a preparation method thereof. Background Art

[0002] As the lightest metal structural material, magnesium alloy has a density of only 2 / 3 of aluminum and 1 / 4 of steel. It has the advantages of high specific strength, easy processing, good thermal and electrical conductivity, excellent shock absorption and electromagnetic shielding properties, as well as good biocompatibility and degradability. It has been widely used in aerospace, automobile manufacturing, consumer electronics and biomedical fields. Although magnesium alloy has many excellent physical and mechanical properties, its corrosion resistance is poor, especially in humid and salty environments. Its corrosion resistance is not as good as that of aluminum alloy and steel materials, which greatly limits the practical application of magnesium alloy. This is because, on the one hand, magnesium has active chemical properties and has the lowest standard electrode potential (-2.37 V / SHE) among structural metals, which makes it very easy to galvanically corrode with the cathode phase or other metals. Secondly, the PBR (Pilling-Bedworth ratio) of the MgO oxide film on the magnesium surface is 0.81, which is less than 1, that is, the volume of the oxide formed on the magnesium surface is smaller than the volume of the metal consumed, and the oxide film cannot cover the magnesium surface densely and completely. Therefore, in an environment containing chloride, chloride ions can easily destroy the oxide film on the surface of magnesium and induce severe local pitting, which can lead to severe corrosion of magnesium alloys. For example, commercial AZ91 alloy is prone to local pitting. Pitting can also lead to a rapid decline in the mechanical properties of magnesium alloys, resulting in premature aging of the alloy. Therefore, local pitting should be avoided as much as possible.

[0003] At present, the method for improving the corrosion resistance of magnesium alloys usually adopts the surface treatment method. For example, in CN105970170B, Hf coating and Si3N4 coating are alternately deposited to prepare Hf / Si3N4 multilayer structure coating with good conductivity and corrosion resistance. This coating can effectively block the continuous growth of columnar defects and change the growth orientation of the coating. At the same time, it significantly reduces the corrosion rate of the magnesium alloy substrate and improves the corrosion resistance of the magnesium alloy. However, the stability and durability of the surface coating is still a challenge. Under the action of external force, the coating is very easy to peel off and break, resulting in a decrease in corrosion resistance. In addition, it may also cause local corrosion at the damaged coating.

[0004] Therefore, developing magnesium alloys with high bulk corrosion resistance is the most direct and effective way to improve the corrosion resistance of magnesium alloys and is the key to achieving large-scale application of magnesium alloys. Summary of the invention

[0005] The purpose of the present invention is to provide a high corrosion-resistant magnesium alloy plate with filiform corrosion characteristics and a preparation method thereof. The method combines alloy composition design with microstructure regulation, and by inhibiting local pitting corrosion of the alloy, the alloy exhibits filiform corrosion characteristics that develop along the surface of the substrate. This filiform corrosion can effectively slow down the expansion rate of corrosion, unlike local pitting corrosion, which causes accelerated corrosion. In addition, filiform corrosion only expands on the surface of the alloy and does not penetrate into the interior of the alloy, thereby maintaining the integrity of the material and avoiding premature failure of the alloy.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a high corrosion resistant magnesium alloy plate having filiform corrosion characteristics, wherein the magnesium alloy plate contains the following elements by mass percentage based on the total amount of the magnesium alloy plate: Al: 6-9%, Sc: 0.05-0.15%, Y: 0.05-0.15%, Mn: 0.05-0.15%, and the balance is Mg and unavoidable impurity elements; wherein the magnesium alloy plate has a dispersed Mg 17 Al 12 The phase structure of the phase.

[0007] The magnesium alloy sheet in the present invention has excellent corrosion resistance. It is based on the low-cost Mg-Al alloy and a small amount of Sc and Y elements with high solid solubility are added to make the magnesium alloy sheet have excellent corrosion resistance. This may be because by adding a small amount of Sc and Y elements with high solid solubility, on the one hand, the alloy elements can be dissolved into the magnesium matrix as much as possible to improve the chemical stability of the matrix, thereby avoiding the formation of a large number of high-potential second phases to weaken the micro-galvanic corrosion of the magnesium matrix; on the other hand, the oxides Sc2O3 and Y2O3 formed by the Sc and Y elements have a PBR of 1.19 and 1.28, which can effectively fill the compactness of the MgO oxide film and improve the protective performance of the oxide film. In addition, the doping of Sc2O3 and Y2O3 in the oxide film can effectively improve the chemical and physical blocking ability of the oxide film to chloride ions, and reduce the adsorption capacity of chloride ions to the oxide film. In addition, the addition of rare earth elements Sc and Y can purify the melt and reduce the influence of impurity elements on corrosion resistance. At the same time, the addition of Mn elements can increase the allowable limit of impurity Fe in the magnesium-aluminum alloy and reduce the content of impurity Fe.

[0008] In order to avoid the influence of impurity elements on the performance of the magnesium alloy sheet in the present invention, further, based on the total amount of the magnesium alloy sheet, the mass content of the unavoidable impurity elements is less than 0.02%.

[0009] The inevitable impurities in the present invention refer to other impurity elements except Mg, Al, Sc, Y, and Mn. In some embodiments, the inevitable impurity elements include at least one of Fe, Ni, and Cu. This embodiment is only an exemplary description of the type of impurities, and the present invention is not limited thereto.

[0010] In one embodiment of the present invention, a high corrosion-resistant magnesium alloy plate having filiform corrosion characteristics is provided. The magnesium alloy plate contains the following elements, based on the total amount of the magnesium alloy plate and in terms of mass percentage: Al: 8%, Sc: 0.1%, Y: 0.1%, Mn: 0.1%, and inevitable impurity elements include Fe, Cu and Ni impurity elements. The total content of the inevitable impurity elements is less than 0.02%, and the balance is Mg.

[0011] In one embodiment of the present invention, a high corrosion-resistant magnesium alloy plate having filiform corrosion characteristics is provided. The total amount of the magnesium alloy plate is taken as a basis, and in terms of mass percentage, the magnesium alloy plate contains the following elements: Al: 8%, Sc: 0.15%, Y: 0.15%, Mn: 0.15%, and the inevitable impurity elements include Fe, Cu and Ni impurity elements. The total content of the inevitable impurity elements is less than 0.02%, and the balance is Mg.

[0012] In one embodiment of the present invention, a high corrosion-resistant magnesium alloy plate having filiform corrosion characteristics is provided. The total amount of the magnesium alloy plate is taken as a basis, and in terms of mass percentage, the magnesium alloy plate contains the following elements: Al: 8%, Sc: 0.10%, Y: 0.10%, Mn: 0.10%, and the inevitable impurity elements include Fe, Cu and Ni impurity elements. The total content of the inevitable impurity elements is less than 0.02%, and the balance is Mg.

[0013] The dispersed Mg in the present invention 17 Al 12 Phase refers to Mg 17 Al 12 The phase has a fine structure and is dispersed in the phase structure, rather than being dispersed in a coarse network in the phase structure. The magnesium alloy sheet of the present invention has a dispersed Mg 17 Al 12 The phase can better improve the corrosion resistance of magnesium alloy sheets, which may be due to the fine dispersed Mg 17 Al 12 The presence of phase can effectively weaken the Mg 17 Al 12 Microgalvanic effect relative to the magnesium matrix. 17 Al 12 As the cathode phase, it is more inert to chloride ions, and the fine and densely dispersed Mg 17 Al12 The phase can effectively prevent the extension of local corrosion to a deeper level, thereby avoiding the occurrence of local pitting corrosion, and its corrosion form is a typical filamentary corrosion morphology.

[0014] The magnesium alloy sheet in the present invention is an alloy material based on Mg-Al alloy, formed by adding small amounts of Sc, Y and Mn elements. Specifically, the phase structure of the magnesium alloy sheet in the present invention is mainly an α-Mg phase structure, which may also contain Al2Y phase and Al8Mn4Y phase.

[0015] The density of the magnesium alloy sheet in the present invention is 1.8 g / cm 3 The elastic modulus is around 46 GPa, and the crystal structure is a multiphase structure, in which the magnesium matrix is ​​a close-packed hexagonal crystal structure.

[0016] In a second aspect, the present invention provides a method for preparing the high corrosion resistant magnesium alloy plate having filiform corrosion characteristics according to the first aspect of the present invention, the preparation method comprising: (1) Pure magnesium ingots, pure aluminum, Mg-Sc master alloy, Mg-Y master alloy and Mg-Mn master alloy are weighed according to the element content of the magnesium alloy plate, and then preheated respectively; (2) adding the preheated pure magnesium, pure aluminum, Mg-Sc master alloy, Mg-Y master alloy and Mg-Mn master alloy into a crucible in sequence for smelting under the protection of CO2 and SF6 to obtain a magnesium alloy melt; (3) refining the magnesium alloy melt in step (2) under the protection of CO2 and SF6 gas and in the presence of a refining agent, and then subjecting the molten magnesium alloy to a static insulation treatment to obtain a purified molten magnesium alloy; (4) Under the protection of CO2 and SF6, the purified magnesium alloy melt is subjected to slag removal treatment, and then the slag-removed magnesium alloy melt is cast into a preheated metal mold to obtain a magnesium alloy ingot; (5) Solution treating the magnesium alloy ingot and then extruding it into a plate; (6) performing at least two rolling processes on the plate to obtain a rolled plate; (7) The rolled plate is subjected to aging treatment to obtain the final high corrosion-resistant magnesium alloy plate.

[0017] The Mg-Sc master alloy that can be cited in the present invention is Mg-30Sc master alloy, wherein Mg-30Sc refers to an alloy containing 30wt% Sc, and the remainder is Mg and inevitable impurity elements.

[0018] The Mg-Y master alloy that can be cited in the present invention is Mg-30Y master alloy, wherein Mg-30Y refers to an alloy containing 30wt% Y, and the remainder is Mg and inevitable impurity elements.

[0019] The Mg-Mn master alloy that can be cited in the present invention is Mg-5Mn master alloy, wherein Mg-5Mn refers to an alloy containing 5wt% of Mn, and the remainder being Mg and inevitable impurity elements.

[0020] In the present invention, the purpose of preheating is to remove the moisture that may be contained in the raw materials. Furthermore, the conditions of the preheating include: a preheating temperature of 200-300° C. and a preheating time of 1-3 hours.

[0021] Furthermore, in steps (2), (3) and (4), the volume ratio of SF6 and CO2 in the protective gas is independently 1:(5-12), for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, preferably 1:9.

[0022] Furthermore, in step (2): adding a pure magnesium ingot at 590-620°C and heating to 680-690°C to melt the pure magnesium ingot; adding a Mg-Mn master alloy at 695-710°C, then heating to 715-740°C and adding a pure aluminum ingot; then raising the temperature to 745-780°C and sequentially adding a Mg-Sc master alloy and a Mg-Y master alloy, and then keeping the temperature until all the raw materials are melted, thereby obtaining the magnesium alloy melt.

[0023] Furthermore, in step (2): a pure magnesium ingot is added at 600°C and heated to 690°C to melt the pure magnesium ingot; a Mg-Mn master alloy is added at 700°C, and then heated to 720°C and a pure aluminum ingot is added; then the temperature is raised to 750°C and Mg-Sc master alloy and Mg-Y master alloy are added in sequence, and then the temperature is kept constant until all raw materials are melted to obtain the magnesium alloy melt.

[0024] The crucible in the present invention can be a conventional stainless steel crucible coated with a coating in the art.

[0025] Furthermore, in step (3), the amount of the refining agent is 0.05-0.3 wt% of the mass of the magnesium alloy melt, for example, 0.05 wt%, 0.08 wt%, 0.1 wt%, 0.12 wt%, 0.15 wt%, 0.18 wt%, 0.2 wt%, 0.25 wt%, 0.3 wt%, and preferably 0.12 wt%.

[0026] Furthermore, in step (3), the refining agent includes metal chloride and fluoride.

[0027] Furthermore, the mass ratio of the metal chloride to the fluoride is (10-20):1, for example, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, preferably (15-16):1.

[0028] Further, the metal chloride comprises a combination of KCl, CaCl2, BaCl2 and YCl3.

[0029] Furthermore, the mass ratio of KCl, CaCl2, BaCl2 and YCl3 is (5-8):(3-4):(1.5-2.5):1.

[0030] Furthermore, the fluoride is selected from CaF.

[0031] Furthermore, the refining agent also includes 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide, preferably 1-C6-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide.

[0032] 1-C6-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide that can be listed in the present invention include 1-hexyl-3-methylimidazolium hexafluorophosphate modified graphene oxide, 1-hexyl-3-methylimidazolium hexafluorophosphate modified graphene oxide, 1-heptyl-3-methylimidazolium hexafluorophosphate modified graphene oxide, 1-octyl-3-methylimidazolium hexafluorophosphate modified graphene oxide, 1-dodecyl-3-methylimidazolium hexafluorophosphate modified graphene oxide, and the like.

[0033] Furthermore, the mass ratio of the 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide (preferably 1-C6-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide) to the fluoride is (1-1.5):1, for example, 1:1, 1.2:1, 1.25:1, 1.3:1, 1.4:1, 1.5:1.

[0034] The use of metal chloride and fluoride in the present invention can purify the melt and remove impurities to a certain extent. When the refining agent contains a certain amount of 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide, the comprehensive performance of the magnesium alloy plate can be better increased. It is speculated that this may be because YCl3 can form rare earth composite inclusions with other impurity components, and the specific gravity of the rare earth composite inclusions is close to that of the melt, and it is difficult to precipitate from the melt. The 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide has a certain adsorption property. On the one hand, the rare earth composite inclusions can be precipitated from the melt through adsorption. On the other hand, the surface tension between the rare earth composite inclusions and the alloy liquid makes the refining agent form The complex inclusions and alloy liquid are easy to separate, thereby reducing the impurity content. At the same time, it can also increase the number of crystal cores in the metal liquid, refine the grains, and thus better increase the strength and corrosion resistance of the alloy. At the same time, it works together with other components to significantly reduce the non-metallic oxide and hydrogen content, increase the elongation and corrosion resistance, and further studies have found that the use of 1-C6-C12 alkyl-3-methylimidazole hexafluorophosphate to modify graphene oxide can better increase the comprehensive performance of the alloy. This may be because the modified carbon chain length within a suitable range helps to enhance the interaction between the modified graphene and other refined components. When the carbon chain length is too short, the interaction is poor. When the carbon chain length is too long, the adsorption of the modified graphene will be poor.

[0035] Furthermore, the preparation method of the 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide includes: dispersing graphene oxide in water to form a suspension, then adding 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate, reacting at 20-30°C for 2-5 hours, then centrifuging, discarding the supernatant, and drying the solid to obtain 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide.

[0036] Furthermore, when preparing 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide, the graphene oxide is a single-layer graphene oxide with an average sheet diameter of 0.5-5 μm and an average thickness of 0.8-1.2 nm.

[0037] The graphene oxide in the present invention can be obtained commercially, preferably a single-layer graphene oxide purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd., with an average sheet diameter of 2.5 μm and an average thickness of 1 nm.

[0038] Furthermore, when preparing 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide, the mass ratio of graphene oxide to water is 1:(8-12).

[0039] Furthermore, when preparing 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide, the weight ratio of graphene oxide to 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate is 1:(0.05-0.2), preferably 1:(0.1-0.12).

[0040] Furthermore, when preparing 1-C3-C12 alkyl-3-methylimidazolium hexafluorophosphate modified graphene oxide, the drying conditions include: drying at 105-120° C. for 2-5 h.

[0041] Furthermore, in step (3), the refining agent is added at a temperature of 740-750°C (preferably 750°C) while being manually stirred, and the refining is continued for 5-20 minutes after the addition of the refining agent. The aforementioned manual stirring is a conventional stirring means in the art, and its purpose is to allow the refining agent to fully react with impurities in the melt.

[0042] Furthermore, in step (3), the conditions for standing and keeping warm include: first standing at 740-750°C for 30-40 minutes, then cooling to 705-720°C (preferably 710°C) and standing for 20-30 minutes.

[0043] Furthermore, the slag removal treatment in step (4) is a conventional operation method in the art, and the conditions for the slag removal treatment include: reducing the temperature to 690-700°C (preferably 690°C) to remove the slag on the surface of the melt.

[0044] Furthermore, in step (4), the casting temperature is 690-700°C, and the metal mold preheating temperature is 190-210°C (preferably 200°C).

[0045] Furthermore, in step (5), the conditions for the solution treatment include: a temperature of 400-420° C. and a time of 18-32 hours (preferably 24 hours).

[0046] Furthermore, in step (5), the extrusion conditions include: extrusion temperature 350-390°C, extrusion speed 0.5-1 m / min, and extrusion ratio 15:1-20:1.

[0047] Furthermore, in step (6), the plate is subjected to three rolling processes to obtain a rolled plate.

[0048] Furthermore, in step (6), the conditions of each rolling treatment include: a rolling temperature of 250-300°C, a single-pass pressing amount of 4-6% (preferably 5%), a total pressing amount of 12-18% (preferably 15%), and an initial thickness of the extruded plate of 8-12 mm.

[0049] The present invention can effectively refine the grains and break the coarse Mg mesh by extrusion and multi-pass rolling deformation treatment. 17 Al 12 phase, thereby significantly improving the mechanical properties of the alloy and reducing the micro-galvanic corrosion effect of the coarse network phase. In addition, multi-pass rolling treatment can provide a precipitation driving force for the subsequent aging treatment by introducing a large number of dislocations and twin crystal defects, promoting the precipitation of fine dispersed Mg 17 Al 12 The rapid formation of phase. Due to the addition of Sc and Y elements and a large number of fine dispersed Mg 17 Al 12 The presence of the phase makes the alloy exhibit filamentary corrosion characteristics, effectively avoiding the occurrence of local pitting corrosion, thereby significantly improving the corrosion resistance of the alloy. 17 Al 12 The presence of phase can effectively weaken the Mg 17 Al 12 Microgalvanic effect relative to the magnesium matrix. 17 Al 12 As the cathode phase, it is more inert to chloride ions, and the fine and densely dispersed Mg 17 Al 12 The phase can effectively prevent the local corrosion from extending to the depth, thus avoiding the occurrence of local pitting corrosion. 17 Al 12 Severe local pitting caused by phase.

[0050] Furthermore, in step (7), the aging treatment conditions include: aging temperature of 175-200° C., and aging time of 12-48 hours.

[0051] Compared with the prior art, the advantages and beneficial effects of the present invention are: The present invention adopts low-cost Mg-Al alloy as the basis, adds a small amount of rare earth elements Sc and Y, and has the advantage of low cost. At the same time, compared with other surface coatings, the magnesium alloy of the present invention can be realized through alloying and conventional smelting, extrusion, rolling and heat treatment processes, without complicated surface treatment, and is suitable for large-scale production. At the same time, the alloy of the present invention has excellent corrosion resistance while taking into account excellent mechanical properties. The magnesium alloy of the present application can not only be used in 3C electronic products, such as laptop computer casings, but also can be used under harsh conditions such as high humidity and salt spray, especially in complex sports environments such as marine engineering and transportation. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is the SEM image of the microstructure of the magnesium alloy prepared in Example 1.

[0053] Figure 2 This is a SEM image of the surface corrosion morphology of the magnesium alloy in Example 1 immersed in a 3.5 wt% NaCl solution for 7 days; Figure 3 This is a SEM image of the surface corrosion morphology of the magnesium alloy in Comparative Example 1 immersed in a 3.5 wt% NaCl solution for 7 days.

[0054] Figure 4 This is a SEM image of the cross-sectional corrosion morphology of the magnesium alloy in Comparative Example 3 immersed in a 3.5 wt% NaCl solution for 7 days. DETAILED DESCRIPTION

[0055] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] Example 1 This embodiment provides a method for preparing a magnesium alloy plate, the preparation method comprising: (1) Pure magnesium ingot, pure aluminum, Mg-30Sc master alloy, Mg-30Y master alloy and Mg-5Mn master alloy were weighed according to the element content of the magnesium alloy plate, and then preheated at 300°C for 2 hours to remove moisture; (2) Under the protective gas of CO2 and SF6 with a volume ratio of 1:9, pure magnesium ingot is added at 600°C and heated to 690°C to melt the pure magnesium ingot; Mg-5Mn master alloy is added at 700°C, and then heated to 720°C and pure aluminum ingot is added; then the temperature is raised to 750°C and Mg-30Sc master alloy and Mg-30Y master alloy are added in sequence, and then the temperature is kept until all raw materials are melted to obtain a magnesium alloy melt; (3) Adding a refining agent to the magnesium alloy melt at a temperature of 750°C under a protective gas atmosphere of CO2 and SF6 in a volume ratio of 1:9, stirring manually while adding the refining agent, and continuing stirring for 10 minutes after the addition of the refining agent, then standing at 750°C for 35 minutes, and then cooling to 710°C and standing for 25 minutes to obtain a purified magnesium alloy melt; (4) Under the protective gas of CO2 and SF6 with a volume ratio of 1:9, the temperature is lowered to 690°C to remove the slag on the surface of the purified magnesium alloy melt, and then the melt is cast at 690°C into a metal mold preheated at 200°C to obtain a magnesium alloy ingot; (5) The magnesium alloy ingot was solution treated at 420°C for 24 hours and then extruded into a plate (the extrusion conditions included: extrusion temperature 350°C, extrusion speed 1 m / min, extrusion ratio 15:1); (6) The plate is subjected to three rolling processes to obtain a rolled plate; the conditions of each rolling process include: a rolling temperature of 270° C., a single-pass pressing amount of 5%, a total pressing amount of 15%, and an initial thickness of the extruded plate of 10 mm; (7) The rolled plate is subjected to aging treatment (aging temperature 175° C., aging time 16 hours) to obtain the highly corrosion-resistant magnesium alloy plate.

[0057] In step (1), by mass percentage, Al: 8%, Sc: 0.1%, Y: 0.1%, Mn: 0.1%, the total content of Fe, Cu, and Ni impurity elements is less than 0.02%, and the balance is Mg, and the corresponding pure magnesium ingot, pure aluminum, Mg-Sc master alloy, Mg-Y master alloy, and Mg-Mn master alloy are weighed; In step (3): the amount of the refining agent is 0.12 wt% of the mass of the magnesium alloy melt; the refining agent is metal chloride and fluoride; the mass ratio of the metal chloride to the fluoride is 15.67:1; the metal chloride is a combination of KCl, CaCl2, BaCl2 and YCl3, and the mass ratio thereof is 7:3.43:2:1; the fluoride is selected from CaF.

[0058] After testing, the chemical composition of the magnesium alloy in this embodiment is as follows: Al 8.15 wt%, Sc 0.10 wt%, Y 0.11 wt%, Mn 0.12 wt%, and inevitable impurities include: Fe 0.0053 wt%, Ni 0.0004 wt%, Cu 0.0005 wt%, and the balance is Mg.

[0059] The microstructure SEM image of the magnesium alloy prepared in this embodiment is as follows: Figure 1 As shown, through Figure 1 It can be seen that the magnesium alloy has finely dispersed Mg 17 Al 12 Phase distributed in the magnesium matrix, Mg 17 Al 12 The phase is distributed in rod and needle shapes, with a size of about a few microns. The uniformly dispersed Mg 17 Al 12 phase can significantly improve the mechanical properties of the alloy through precipitation strengthening. 17 Al 12 Compared with the traditional network of coarse Mg 17 Al 12Compared with the phase, the microgalvanic corrosion effect of the second phase on the magnesium matrix can be greatly weakened, so that the alloy changes from severe local pitting to slight filamentary corrosion behavior, significantly improving the corrosion resistance of the alloy. Specifically, the smaller the size of the second phase, the smaller the microgalvanic acceleration of the magnesium matrix, and the uniform distribution of the second phase can further promote the uniform distribution of microgalvanic current in the matrix, avoiding local current concentration, thereby avoiding the occurrence of local pitting. In addition, we found that the finely dispersed Mg 17 Al 12 The phase can prevent the corrosion from penetrating and make the alloy present a worm-like surface corrosion morphology.

[0060] Example 1 The corrosion surface morphology after immersion in the corrosive medium for 7 days is as follows Figure 2 It can be found that the corrosion products on the alloy surface are distributed on the surface like worms, and it can be seen that the wire width is about tens of microns, the corrosion is relatively slight, and no local pitting occurs, indicating that the alloy has excellent corrosion resistance. In addition, it can be found that the Sc and Y elements added in the present invention make the corrosion products on the alloy surface more uniform and dense, effectively blocking the invasion of corrosive media.

[0061] Example 2 This embodiment provides a method for preparing a magnesium alloy plate, the preparation method comprising: (1) Pure magnesium ingot, pure aluminum, Mg-30Sc master alloy, Mg-30Y master alloy and Mg-5Mn master alloy were weighed according to the element content of the magnesium alloy plate, and then preheated at 300°C for 2 hours to remove moisture; (2) Under the protective gas of CO2 and SF6 with a volume ratio of 1:9, pure magnesium ingot is added at 600°C and heated to 690°C to melt the pure magnesium ingot; Mg-5Mn master alloy is added at 700°C, and then heated to 720°C and pure aluminum ingot is added; then the temperature is raised to 750°C and Mg-30Sc master alloy and Mg-30Y master alloy are added in sequence, and then the temperature is kept until all raw materials are melted to obtain a magnesium alloy melt; (3) Adding a refining agent to the magnesium alloy melt at a temperature of 750°C under a protective gas atmosphere of CO2 and SF6 in a volume ratio of 1:9, stirring manually while adding the refining agent, and continuing stirring for 10 minutes after the addition of the refining agent, then standing at 750°C for 35 minutes, and then cooling to 710°C and standing for 25 minutes to obtain a purified magnesium alloy melt; (4) Under the protective gas of CO2 and SF6 with a volume ratio of 1:9, the temperature is lowered to 690°C to remove the slag on the surface of the purified magnesium alloy melt, and then the melt is cast at 690°C into a metal mold preheated at 200°C to obtain a magnesium alloy ingot; (5) The magnesium alloy ingot is solution treated at 420°C for 24 hours and then extruded into a plate; (6) The plate is subjected to three rolling processes to obtain a rolled plate; the conditions of each rolling process include: a rolling temperature of 270° C., a single-pass pressing amount of 5%, a total pressing amount of 15%, and an initial thickness of the extruded plate of 10 mm; (7) The rolled plate is subjected to aging treatment (aging temperature is 175°C, aging time is 16 hours) to obtain the obtained product.

[0062] In step (1), by mass percentage, Al: 8%, Sc: 0.15%, Y: 0.15%, Mn: 0.15%, unavoidable impurity elements are less than 0.02%, and the balance is Mg, and the corresponding pure magnesium ingot, pure aluminum, Mg-Sc master alloy, Mg-Y master alloy and Mg-Mn master alloy are weighed; the preheating conditions include: the preheating temperature is 360° C., and the preheating time is 2 hours; In step (3): the amount of the refining agent is 0.12 wt% of the mass of the magnesium alloy melt; the refining agent is metal chloride and fluoride; the mass ratio of the metal chloride to the fluoride is 15.67:1; the metal chloride is a combination of KCl, CaCl2, BaCl and YCl3, and the mass ratio thereof is 7:3.43:2:1; the fluoride is selected from CaF.

[0063] After testing, the chemical composition of the magnesium alloy in this embodiment is as follows: Al 8.06 wt%, Sc 0.14 wt%, Y 0.15 wt%, Mn 0.14 wt%, and inevitable impurities include: Fe 0.0057 wt%, Ni 0.0006 wt%, Cu 0.0004 wt%, and the balance is Mg.

[0064] The microstructure SEM image of the magnesium alloy prepared in this example is similar to Figure 1 Similarly, magnesium alloys with finely dispersed Mg 17 Al 12 Mutually.

[0065] Example 3 This embodiment provides a method for preparing a magnesium alloy plate, the method comprising: (1) Pure magnesium ingot, pure aluminum, Mg-30Sc master alloy, Mg-30Y master alloy and Mg-5Mn master alloy were weighed according to the element content of the magnesium alloy plate, and then preheated at 300°C for 2 hours to remove moisture; (2) Under the protective gas of CO2 and SF6 with a volume ratio of 1:9, pure magnesium ingot is added at 600°C and heated to 690°C to melt the pure magnesium ingot; Mg-5Mn master alloy is added at 700°C, and then heated to 720°C and pure aluminum ingot is added; then the temperature is raised to 750°C and Mg-30Sc master alloy and Mg-30Y master alloy are added in sequence, and then the temperature is kept until all raw materials are melted to obtain a magnesium alloy melt; (3) Adding a refining agent to the magnesium alloy melt at a temperature of 750°C under a protective gas atmosphere of CO2 and SF6 in a volume ratio of 1:9, stirring manually while adding the refining agent, and continuing stirring for 10 minutes after the addition of the refining agent, then standing at 750°C for 35 minutes, and then cooling to 710°C and standing for 25 minutes to obtain a purified magnesium alloy melt; (4) Under the protective gas of CO2 and SF6 with a volume ratio of 1:9, the temperature is lowered to 690°C to remove the slag on the surface of the purified magnesium alloy melt, and then the melt is cast at 690°C into a metal mold preheated at 200°C to obtain a magnesium alloy ingot; (5) The magnesium alloy ingot was solution treated at 420°C for 24 hours and then extruded into a plate (the extrusion conditions included: extrusion temperature 350°C, extrusion speed 1 m / min, extrusion ratio 15:1); (6) The plate is subjected to three rolling processes to obtain a rolled plate; the conditions of each rolling process include: a rolling temperature of 270°C, a single-pass pressing amount of 4%, a total pressing amount of 12%, and an initial thickness of the extruded plate of 10 mm; (7) The rolled plate is subjected to aging treatment (aging temperature is 200°C, aging time is 24 hours) to obtain the obtained product.

[0066] In step (1), by mass percentage, Al: 8%, Sc: 0.10%, Y: 0.10%, Mn: 0.10%, unavoidable impurity elements are less than 0.02%, and the balance is Mg, and the corresponding pure magnesium ingot, pure aluminum, Mg-Sc master alloy, Mg-Y master alloy and Mg-Mn master alloy are weighed; the preheating conditions include: the preheating temperature is 360° C., and the preheating time is 2 hours; In step (3): the amount of the refining agent is 0.12 wt% of the mass of the magnesium alloy melt; the refining agent is metal chloride and fluoride; the mass ratio of the metal chloride to the fluoride is 15.67:1; the metal chloride is a combination of KCl, CaCl2, BaCl and YCl3, and the mass ratio thereof is 7:3.43:2:1; the fluoride is selected from CaF.

[0067] After testing, the chemical composition of the magnesium alloy in this embodiment is as follows: Al 7.96 wt%, Sc 0.11 wt%, Y 0.10 wt%, Mn 0.13 wt%, and inevitable impurities include: Fe 0.0062 wt%, Ni 0.0010 wt%, Cu 0.0006 wt%, and the balance is Mg.

[0068] The microstructure SEM image of the magnesium alloy prepared in this example is similar to Figure 1 Similarly, magnesium alloys with finely dispersed Mg 17 Al 12 Mutually.

[0069] Example 4 The difference between this embodiment and embodiment 1 is: The refining agent is metal chloride, fluoride, and 1-octyl-3-methylimidazolium hexafluorophosphate modified graphene oxide; the mass ratio of metal chloride, fluoride and 1-octyl-3-methylimidazolium hexafluorophosphate modified graphene oxide is 15.67:1:1.52; the metal chloride is a combination of KCl, CaCl2, BaCl and YCl3, and the mass ratio is 7:3.43:2:1; the fluoride is selected from CaF; The preparation method of 1-octyl-3-methylimidazolium hexafluorophosphate modified graphene oxide is as follows: graphene oxide is dispersed in water to form a suspension, then 1-octyl-3-methylimidazolium hexafluorophosphate is added, reacted at 25°C for 4 hours, then centrifuged, the supernatant is discarded, and the solid is dried to obtain 1-octyl-3-methylimidazolium hexafluorophosphate modified graphene oxide; wherein the graphene oxide is a single-layer graphene oxide purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd., and its average sheet diameter is 2.5 μm and the average thickness is 1 nm; the mass ratio of graphene oxide to water is 1:10; the weight ratio of graphene oxide to 1-octyl-3-methylimidazolium hexafluorophosphate is 1:0.12; and the drying conditions include: drying at 110°C for 3 hours.

[0070] After testing, the chemical composition of the magnesium alloy in this embodiment is as follows: Al 8.12 wt%, Sc 0.11 wt%, Y 0.12 wt%, Mn 0.10 wt%, and inevitable impurities include: Fe 0.0018 wt%, Ni 0.0002 wt%, Cu 0.0003 wt%, and the balance is Mg.

[0071] The microstructure SEM image of the magnesium alloy prepared in this example is similar to Figure 1 Similarly, magnesium alloys with finely dispersed Mg 17 Al 12 Mutually.

[0072] Example 5 The difference between this embodiment and embodiment 4 is: The 1-octyl-3-methylimidazolium hexafluorophosphate-modified graphene oxide is replaced by 1-hexyl-3-methylimidazolium hexafluorophosphate-modified graphene oxide; the preparation method of 1-hexyl-3-methylimidazolium hexafluorophosphate-modified graphene oxide is the same as that of Example 4, except that 1-octyl-3-methylimidazolium hexafluorophosphate is replaced by 1-hexyl-3-methylimidazolium hexafluorophosphate during the preparation.

[0073] After testing, the chemical composition of the magnesium alloy in this embodiment is as follows: Al 8.11 wt%, Sc 0.12 wt%, Y 0.10 wt%, Mn 0.10 wt%, and inevitable impurities include: Fe 0.0022 wt%, Ni 0.0005 wt%, Cu 0.0006 wt%, and the balance is Mg.

[0074] The microstructure SEM image of the magnesium alloy prepared in this example is similar to Figure 1 Similarly, magnesium alloys with finely dispersed Mg 17 Al 12 Mutually.

[0075] Example 6 The difference between this embodiment and embodiment 4 is: The 1-octyl-3-methylimidazolium hexafluorophosphate-modified graphene oxide was replaced by graphene oxide (graphene oxide was purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd. as a single-layer graphene oxide with an average sheet diameter of 2.5 μm and an average thickness of 1 nm).

[0076] After testing, the chemical composition of the magnesium alloy in this embodiment is as follows: Al 8.21 wt%, Sc 0.11 wt%, Y 0.15 wt%, Mn 0.13 wt%, and inevitable impurities include: Fe 0.0048 wt%, Ni 0.0003 wt%, Cu 0.0006 wt%, and the balance is Mg.

[0077] The microstructure SEM image of the magnesium alloy prepared in this example is similar to Figure 1 Similarly, magnesium alloys with finely dispersed Mg 17 Al 12 Mutually.

[0078] Example 7 The difference between this embodiment and embodiment 4 is: The 1-octyl-3-methylimidazolium hexafluorophosphate-modified graphene oxide is replaced by 1-hexadecyl-3-methylimidazolium hexafluorophosphate-modified graphene oxide; the preparation method of 1-hexadecyl-3-methylimidazolium hexafluorophosphate-modified graphene oxide is the same as that of Example 4, except that 1-octyl-3-methylimidazolium hexafluorophosphate is replaced by 1-hexadecyl-3-methylimidazolium hexafluorophosphate during the preparation.

[0079] After testing, the chemical composition of the magnesium alloy in this embodiment is as follows: Al 8.17 wt%, Sc 0.11 wt%, Y 0.10 wt%, Mn 0.13 wt%, and inevitable impurities include: Fe 0.0046 wt%, Ni 0.0003 wt%, Cu 0.0004 wt%, and the balance is Mg.

[0080] The microstructure SEM image of the magnesium alloy prepared in this example is similar to Figure 1 Similarly, magnesium alloys with finely dispersed Mg 17 Al 12 Mutually.

[0081] Example 8 The difference between this embodiment and embodiment 4 is: The 1-octyl-3-methylimidazolium hexafluorophosphate-modified graphene oxide is replaced by 1-ethyl-3-methylimidazolium hexafluorophosphate-modified graphene oxide; the preparation method of 1-ethyl-3-methylimidazolium hexafluorophosphate-modified graphene oxide is the same as that of Example 4, except that 1-octyl-3-methylimidazolium hexafluorophosphate is replaced by 1-ethyl-3-methylimidazolium hexafluorophosphate during the preparation.

[0082] After testing, the chemical composition of the magnesium alloy in this embodiment is as follows: Al 8.12 wt%, Sc 0.12 wt%, Y 0.14 wt%, Mn 0.09 wt%, and inevitable impurities include: Fe 0.0046 wt%, Ni 0.0006 wt%, Cu 0.0008 wt%, and the balance is Mg.

[0083] The microstructure SEM image of the magnesium alloy prepared in this example is similar to Figure 1 Similarly, magnesium alloys with finely dispersed Mg 17 Al 12 Mutually.

[0084] Comparative Example 1 The difference between this comparative example and Example 1 is: Step (1) is: weighing pure magnesium ingots and pure aluminum according to the element content of the magnesium alloy plate, and then preheating them at 300° C. for 2 hours to remove moisture; Step (2) is: under the protection gas of CO2 and SF6 with a volume ratio of 1:9, adding a pure magnesium ingot at 600°C, heating to 690°C to melt the pure magnesium ingot, then heating to 720°C and adding a pure aluminum ingot, and then keeping the temperature until all the raw materials are melted to obtain a magnesium alloy melt; In step (1), Al: 8%, the total content of impurity elements Fe, Cu, and Ni is less than 0.02% by mass, and the balance is Mg. The corresponding pure magnesium ingot and pure aluminum are weighed; the preheating conditions include: the preheating temperature is 300° C. and the preheating time is 2 hours.

[0085] After testing, the chemical composition of the magnesium alloy in this comparative example is as follows: Al 8.2 wt%, inevitable impurities include: Fe 0.0078 wt%, Ni 0.0012 wt%, Cu 0.0011 wt%, and the balance is Mg.

[0086] The corrosion surface morphology of this comparative example after immersion in the corrosive medium (3.5 wt% NaCl solution) for 7 days is as follows Figure 3 As shown. It can be seen that the comparative example has serious local corrosion, a large amount of corrosion products are accumulated on the surface, and deep local pitting pits appear on the surface, which will cause the mechanical and corrosion properties of the alloy to age rapidly. It can be found that the comparative example does not show filamentous corrosion characteristics.

[0087] Comparative Example 2 The difference between this comparative example and Example 1 is that in step (7), the aging temperature is 350° C. and the aging time is 1 hour.

[0088] Comparative Example 3 The difference between this comparative example and Example 1 is that the comparative example uses commercial AZ91D magnesium alloy, and the chemical composition of the magnesium alloy is: Al 8.93 wt%, Zn 0.64 wt%, Mn 0.27 wt%, Fe 0.0059 wt%, Ni 0.0015 wt%, and Cu 0.0012 wt%.

[0089] The cross-sectional morphology of the corrosion surface of this comparative example after immersion in the corrosive medium (3.5 wt% NaCl solution) for 7 days is as follows: Figure 4 As shown. It can be seen that due to the presence of coarse network second phase, commercial magnesium alloys suffer from severe local pitting behavior in corrosive media, which seriously deteriorates the mechanical and corrosion resistance of the alloys.

[0090] Comparative Example 4 The difference between this comparative example and Example 1 is that the plate is subjected to a rolling process once to obtain a rolled plate, and the rolling process conditions include: a rolling temperature of 270° C., a single-pass pressing amount of 15%, and an initial thickness of the extruded plate of 10 mm.

[0091] Comparative Example 5 The difference between this comparative example and Example 1 is: Step (1) is: weighing pure magnesium ingot, pure aluminum, Mg-30Y master alloy and Mg-5Mn master alloy according to the element content of the magnesium alloy plate, and then preheating them at 300° C. for 2 hours to remove moisture; Step (2) is: adding Mg-5Mn master alloy at 700°C under the protection gas of CO2 and SF6 with a volume ratio of 1:9, then heating to 720°C and adding pure aluminum ingot; then raising the temperature to 750°C and adding Mg-30Y master alloy, and then keeping the temperature until all raw materials are melted to obtain a magnesium alloy melt; In step (1), by mass percentage, Al: 8%, Y: 0.1%, Mn: 0.1%, the total content of impurity elements Fe, Cu, and Ni is less than 0.02%, and the balance is Mg. The corresponding pure magnesium ingot, pure aluminum, Mg-Y master alloy, and Mg-Mn master alloy are weighed; the preheating conditions include: the preheating temperature is 360° C. and the preheating time is 2 hours.

[0092] After testing, the chemical composition of the magnesium alloy in this comparative example is as follows: Al 8.18 wt%, Y 0.12 wt%, Mn 0.15 wt%, and inevitable impurities include: Fe 0.0062 wt%, Ni 0.0004 wt%, Cu 0.0008 wt%, and the balance is Mg.

[0093] Comparative Example 6 The difference between this comparative example and Example 1 is: Step (1) is: weighing pure magnesium ingot, pure aluminum, Mg-30Sc master alloy and Mg-5Mn master alloy according to the element content of the magnesium alloy plate, and then preheating them at 300° C. for 2 hours to remove moisture; (2) Under the protective gas of CO2 and SF6 with a volume ratio of 1:9, pure magnesium ingot is added at 600°C and heated to 690°C to melt the pure magnesium ingot; Mg-5Mn master alloy is added at 700°C, and then heated to 720°C and pure aluminum ingot is added; then the temperature is raised to 750°C and Mg-30Sc master alloy is added, and then the temperature is kept until all raw materials are melted to obtain a magnesium alloy melt; In step (1), by mass percentage, Al: 8%, Sc: 0.1%, Y: 0.1%, Mn: 0.1%, the total content of impurity elements Fe, Cu, and Ni is less than 0.02%, and the balance is Mg. The corresponding pure magnesium ingot, pure aluminum, Mg-Sc master alloy, and Mg-Mn master alloy are weighed; the preheating conditions include: the preheating temperature is 360° C. and the preheating time is 2 hours.

[0094] After testing, the chemical composition of the magnesium alloy in this embodiment is as follows: Al 8.13 wt%, Sc 0.11 wt%, Mn 0.11 wt%, and inevitable impurities include: Fe 0.0061 wt%, Ni 0.0003 wt%, Cu 0.0004 wt%, and the balance is Mg.

[0095] The corrosion surface morphology of the magnesium alloy in Example 1 after being immersed in a 3.5 wt% NaCl solution for 7 days is as follows: Figure 2 As shown, it shows a slight filamentous corrosion morphology; the surface corrosion morphology of the magnesium alloy in Comparative Example 1 after being immersed in 3.5 wt% NaCl solution for 7 days is as shown Figure 3 As shown, it exhibits severe local pitting morphology. The corrosion cross-sectional morphology of the magnesium alloy in Comparative Example 3 after being immersed in 3.5 wt% NaCl solution for 7 days is shown in FIG. Figure 4 As shown, it has severe local pitting morphology.

[0096] Performance Testing Mechanical properties and corrosion performance tests: The gauge size of the tensile sheet used for mechanical properties testing is 25 × 6 × 2 mm, with three parallel specimens, and the tensile test standard complies with the national standard GB / T228.1-2021.

[0097] The corrosion test solution is a neutral 3.5 wt% NaCl solution, the test temperature is room temperature 25°C, the sample size is 20×20×5mm, and the test time is 7 days. The immersion corrosion test complies with the national standard GB 10124-88. The weight loss rate is calculated by calculating the difference between the weight of the sample before the corrosion test and the weight of the sample after the corrosion test cleaning. Weight loss rate (mg / cm 2 / day) is equal to the weight difference divided by the surface area of ​​the sample divided by the number of test days, which can be converted into the average depth corrosion rate (mm / year) through the formula.

[0098] The volume of hydrogen gas released by magnesium corrosion was equivalent to the volume of hydrogen gas released by magnesium corrosion by recording the reduction of solution in the burette through a simple hydrogen evolution test device. The hydrogen evolution rate (mL / cm 2 / day). The corrosion cleaning agent is 200 g / L CrO3 + 10 g / L AgNO3, which is a general cleaning method for magnesium alloy corrosion products and complies with the national standard GB / T 16545-2015.

[0099] The test results of the mechanical properties and weight loss hydrogen evolution rate of each group of magnesium alloys are shown in Table 1.

[0100] Table 1 Performance test results

[0101] It can be seen from the above performance test results that the magnesium alloys of Examples 1-8 have excellent corrosion resistance and mechanical properties, especially the comprehensive performance of the magnesium alloys of Examples 4-5 is the most outstanding. This is mainly because the invention adopts low-cost Mg-Al alloy as the basis, and by adding a small amount of Sc and Y elements with high solid solubility, on the one hand, the alloy elements can be dissolved into the magnesium matrix as much as possible to improve the chemical stability of the matrix, and the multi-pass rolling treatment can introduce a large number of dislocations and twin crystal defects to provide precipitation driving force for subsequent aging treatment, promote the fine dispersion of Mg 17 Al 12 The rapid formation of the phase, while the refining agent can better reduce the impurity content during the refining process, and it can also increase the heterogeneous nucleation sites in the magnesium liquid, refine the grains, and thus better increase the strength and corrosion resistance of the alloy.

[0102] However, since the necessary technical solutions are not adopted in the comparative examples, the corresponding performance tests are obviously worse than those of the embodiments. In comparative example 1, there are no Sc, Y, and Mn elements, and it can be seen that the mechanical properties and corrosion resistance are reduced, proving that the Sc, Y, and Mn elements have an important influence on the mechanical properties and corrosion resistance of the Mg alloy; in comparative example 2, the preparation and aging process is different, and it can be seen that its mechanical properties are significantly reduced and the corrosion resistance is reduced to a certain extent, proving that the aging process has an influence on the comprehensive properties of the magnesium alloy, especially the mechanical properties; in comparative example 3, the existing commercial AZ91D magnesium alloy is used, and it can be seen that its mechanical properties are significantly reduced and the corrosion resistance is reduced to a certain extent, proving that the magnesium alloy in the present invention can avoid the traditional commercial AZ91 magnesium alloy due to the coarse mesh Mg 17 Al 12 Phase caused severe local pitting corrosion, and at the same time, it has excellent mechanical properties compared with the existing magnesium alloys; in Example 4, a rolling treatment is performed once, and it can be seen that the mechanical properties and corrosion resistance are reduced, which proves that multiple rolling treatments can significantly improve the mechanical properties of the alloy and reduce the microgalvanic corrosion effect of the coarse network phase; in Example 5, there is no Sc element, and it can be seen that the mechanical properties and corrosion resistance are reduced, which proves that the Sc element has an important influence on the mechanical properties and corrosion resistance of the Mg alloy; in Example 6, there is no Y element, and it can be seen that the mechanical properties and corrosion resistance are reduced, which proves that the Y element has an important influence on the mechanical properties and corrosion resistance of the Mg alloy.

[0103] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high corrosion resistant magnesium alloy sheet with filiform corrosion characteristics, characterized in that: Based on the total amount of the magnesium alloy sheet, the magnesium alloy sheet contains the following elements in terms of mass percentage: Al: 6-9%, Sc: 0.05-0.15%, Y: 0.05-0.15%, Mn: 0.05-0.15%, and the balance is Mg and unavoidable impurity elements; wherein the magnesium alloy sheet has a dispersed Mg 17 Al 12 Phase structure of the phase; The preparation method of the high corrosion-resistant magnesium alloy sheet comprises: (1) Pure magnesium ingots, pure aluminum, Mg-Sc master alloy, Mg-Y master alloy and Mg-Mn master alloy are weighed according to the element content of the magnesium alloy plate, and then preheated respectively; (2) adding the preheated pure magnesium, pure aluminum, Mg-Sc master alloy, Mg-Y master alloy and Mg-Mn master alloy into a crucible in sequence for smelting under the protection of CO2 and SF6 to obtain a magnesium alloy melt; (3) refining the magnesium alloy melt in step (2) under the protection of CO2 and SF6 gas and in the presence of a refining agent, and then subjecting the molten magnesium alloy to a static insulation treatment to obtain a purified molten magnesium alloy; (4) Under the protection of CO2 and SF6, the purified magnesium alloy melt is subjected to slag removal treatment, and then the slag-removed magnesium alloy melt is cast into a preheated metal mold to obtain a magnesium alloy ingot; (5) Solution treating the magnesium alloy ingot and then extruding it into a plate; (6) performing at least two rolling processes on the plate to obtain a rolled plate; (7) Performing aging treatment on the rolled plate to obtain a final high corrosion-resistant magnesium alloy plate; the aging treatment conditions include: aging temperature of 175-200° C., and aging time of 12-48 hours.

2. The magnesium alloy sheet according to claim 1, characterized in that: Based on the total amount of the magnesium alloy sheet, the mass content of the inevitable impurity elements is less than 0.02%; the inevitable impurity elements include at least one of Fe, Ni and Cu.

3. The magnesium alloy sheet according to claim 2, characterized in that: The preheating conditions include: a preheating temperature of 320-380° C. and a preheating time of 1-3 hours; in steps (2), (3) and (4), the volume ratio of SF6 and CO2 in the protective gas is independently 1:(5-12).

4. The magnesium alloy sheet material according to claim 3, characterized in that: In step (2): adding a pure magnesium ingot at 590-620°C and heating to 680-690°C to melt the pure magnesium ingot; adding a Mg-Mn master alloy at 695-710°C, then heating to 715-740°C and adding a pure aluminum ingot; then raising the temperature to 745-780°C and sequentially adding a Mg-Sc master alloy and a Mg-Y master alloy, and then keeping the temperature until all the raw materials are melted to obtain the magnesium alloy melt.

5. The magnesium alloy sheet material according to claim 4, characterized in that: In step (3): the amount of the refining agent used is 0.05-0.3wt% of the mass of the magnesium alloy melt; the refining agent includes metal chloride and fluoride.

6. The magnesium alloy sheet material according to claim 5, characterized in that: In step (3), the mass ratio of the metal chloride to the fluoride is (10-20):1; the metal chloride comprises a combination of KCl, CaCl2, BaCl2 and YCl3; and the fluoride is selected from CaF.

7. The magnesium alloy sheet material according to claim 6, characterized in that: In step (3), the refining agent is added at a temperature of 740-750°C while stirring manually, and the refining is continued for 5-20 minutes after the refining agent is added. The conditions for standing and heat preservation include: first standing at 740-750°C for 30-40 minutes, and then cooling to 705-720°C and standing for 20-30 minutes.

8. The magnesium alloy sheet material according to claim 7, characterized in that: In step (4), the conditions for the slag removal treatment include: reducing the temperature to 690-700°C to remove the slag on the surface of the melt; in step (5), the conditions for the solution treatment include: a temperature of 400-420°C and a time of 18-32 hours; in step (5), the conditions for the extrusion include: an extrusion temperature of 350-390°C, an extrusion speed of 0.5-1 m / min, and an extrusion ratio of 15:1-20:

1.

9. The magnesium alloy sheet material according to claim 8, characterized in that: In step (6), the plate is subjected to three rolling processes to obtain a rolled plate; the conditions of each rolling process include: a rolling temperature of 250-300° C., a single-pass pressing amount of 4-6%, a total pressing amount of 12-18%, and an initial thickness of the extruded plate of 8-12 mm.

Citation Information

Patent Citations

  • Corrosion-resistant magnesium alloy and preparation method thereof

    CN114318096A

  • Super-corrosion-resistant high-strength high-plasticity magnesium alloy and preparation method thereof

    CN115449681A

  • High-toughness AZ series magnesium alloy plate and preparation method thereof

    CN115725882A

  • Aluminum-containing high-corrosion-resistance magnesium alloy and preparation method thereof

    CN116837261A

  • Super-corrosion-resistant magnesium alloy and preparation method thereof

    CN116987939A

Cited By

  • High-strength and high-corrosion-resistance magnesium alloy plate and preparation method thereof

    CN120330558A

  • Low-cost high-strength high-corrosion-resistance magnesium alloy and preparation method thereof

    CN120624905A

  • Corrosion-resistant magnesium alloy with self-repairing protection and preparation method of corrosion-resistant magnesium alloy

    CN122446026A